PERGESERAN PERILAKU BERBAHASA ANAK GENERASI ALFA: STUDI KASUS PSIKOLOGI PERKEMBANGAN DI TK PERTIWI 02 CEPOGO - Suryanik; Indah Lestari; Moch. Widjanarko (STKIP Subang, 2025)
The rapid development of digital technology has significantly influenced language development in early childhood, particularly among Alpha Generation children who grow up with intensive exposure to digital media. This study aims to explore the characteristics and shifts in language behavior of Alpha Generation children from a developmental psychology perspective in a kindergarten context. The research employed a qualitative approach with a case study design conducted at TK Pertiwi 02 Cepogo, Jepara Regency. Data were collected through classroom observations, in-depth interviews with teachers and the school principal, and documentation of learning activities. The findings indicate noticeable shifts in children’s language behavior, including the frequent use of short and repetitive utterances, imitation of digital media language styles, and limited expressive language in structured verbal interactions. However, children demonstrated improved language use when engaged in socially interactive activities facilitated by teachers. These results suggest that language development among Alpha Generation children is shaped by the interaction between psychological development, digital media exposure, and the quality of social interaction in the learning environment. The study highlights the importance of adaptive language learning strategies that emphasize meaningful social interaction to support children’s expressive language development in the digital era.